2020
DOI: 10.3390/jcs4020068
|View full text |Cite
|
Sign up to set email alerts
|

Remanufacturing of Woven Carbon Fibre Fabric Production Waste into High Performance Aligned Discontinuous Fibre Composites

Abstract: The composites industry generates considerable volumes of waste in a wide variety of forms, from the production of by-products to end-of-life parts. This paper focuses on the remanufacturing of dry fibre off-cuts, produced during the composite fabric weaving process, into highly aligned discontinuous fibre prepreg tapes with High Performance Discontinuous Fibre (HiPerDiF) technology. Unidirectional laminate specimens are prepared using various combinations of fibre lengths and tested in tension, obtaining a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…The HiPerDiF technology has been used to remanufacture carbon fibres reclaimed both with pyrolytic and solvolytic processes [26,28], as well as manufacturing waste [32], into high performance recycled composites. Moreover, it was used to intermingle rCF and natural fibres to obtain functionalised materials with potential vibration damping applications [27].…”
Section: Background 21 the Hiperdif Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The HiPerDiF technology has been used to remanufacture carbon fibres reclaimed both with pyrolytic and solvolytic processes [26,28], as well as manufacturing waste [32], into high performance recycled composites. Moreover, it was used to intermingle rCF and natural fibres to obtain functionalised materials with potential vibration damping applications [27].…”
Section: Background 21 the Hiperdif Technologymentioning
confidence: 99%
“…The potential value of the HiPerDiF technology in remanufacturing rCFs [26][27][28] aiding the recycling of both thermoset [29] and thermoplastic [30,31] matrix composites, and manufacturing waste [32] within a circular economy framework [29][30][31] has been widely demonstrated, and, if deployed in the right applications, could be a key component to deliver the UK Government's legal commitment for net-zero greenhouse gas (GHG) emissions by 2050 [33]. For industry to achieve this, reliable environmental impact (EI) information based on scientific data must be clearly communicated to customers, government, and wider stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have produced composites by infusing these preforms using manufacturing techniques such as autoclave resin film infusion [34][35][36] and powder or resin film compression molding [37][38][39]. In most studies, fiber length was 3 mm, though fibers of up to 6 mm in length were shown to produce preforms made into composites with adequate mechanical properties [36]. Fiber alignment was high, with 65-67% of fibers aligned within ±3 • of the loading axis.…”
Section: Highly Aligned Preformsmentioning
confidence: 99%
“…It is clear that the fiber dispersion is imperfect, as resin-rich regions exist that strongly influence the strength of the recycled fiber composites. Recently, Aravindan et al [36] used the HiPerDiF method to convert staple MR60H carbon fibers of 3 mm, 4.5 mm, and 6 mm length into highly aligned epoxy composites using autoclave curing. Composites with 41% fiber volume fraction showed good mechanical properties.…”
Section: Highly Aligned Preformsmentioning
confidence: 99%
“…The HiPerDiF method can also address the sustainability of composite materials in terms of manufacturing and recycling. For example, the production of high performance recycled carbon fibre FRP has been demonstrated by remanufacturing reclaimed fibres with the HiPerDiF method [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Lower environmental impact FRP production can be achieved since the method operates with water as the alignment medium, unlike traditional glycerol methods.…”
Section: Introductionmentioning
confidence: 99%